The bird atlas - Taylor, Barbara, 1954-; Orr, Richard (New York : Dorling Kindersley ; Boston : Distributed by Houghton Mifflin Company, 1993)
Describes the physical characteristics and habitats of birds around the world.
How to use this atlas -- What is a bird? Where birds live -- The Arctic -- The Americas. North America, forests and woodlands -- North American western mountains -- North American deserts -- North American wetlands -- North America, Central America and the Caribbean -- South America, Amazon rain forest -- South America, Andes -- South America, Pampas -- South America, Galapagos Islands -- Europe. Forest and woodlands -- Mediterranean -- Coastal areas -- Africa. Forests and mountains -- Savannah -- Wetlands -- Asia. Himalyas. Southeast Asia -- Japan and China -- Australisia. Woodland and desert -- Rain forests -- New Zealand -- Antarctica -- Travelers of the world -- Birds in danger -- Index.
"Dorling Kindersley Book."
Includes index.
Keywords: Birds -- Juvenile literature; Birds -- Geographical distribution -- Juvenile literature; Birds -- Habitat -- Juvenile literature; Birds; Oiseaux -- Ouvrages pour la jeunesse; Oiseaux -- 0; Birds; Birds -- Geographical distribution; Birds -- Habitat; Birds; Birds; Literature; Juvenile works; Literature; Juvenile literature